Relationship between body mass index and postural balance and flexibility in adolescent girls - Lestari, Utami Sasmita; Angmalisang, Elvin Clara; Wijaya, Nur Anindhita Kurniawaty; Wirawanti, Ika Wirya (Science Midwifery, 2024)
Adolescence is a transition period from childhood to adulthood which is marked by many changes. Adolescents generally have a sedentary lifestyle which causes an increase in body mass index. An increase in body mass index has a negative impact on postural balance and flexibility. Excessive fat in the body tends to change the location of the body's center of gravity and limit joint movement. This study aimed to determine the relationship between body mass index and postural balance and flexibility in adolescent girls. This research was a correlation study and used a cross sectional research design with a total of 35 young women. The parameters used to measure postural balance are the Y-balance test and flexibility is the sit-and-reach test. The data analysis used in this research is Pearson correlation analysis. The results showed that there was a significant relationship between body mass index and postural balance (p=0.001) and flexibility (p=0.001) and the level of closeness of the relationship between each variable was very strong (r=0.825). The higher the BMI, the lower the postural balance and flexibility.